Rabindranath Tagore’s Views on Camera, Cinema, and Film Adaptation - Shah Ahmed (Asiatic: IIUM Journal of English Language and Literature, 2022)
From his first exposure to cinema to his engagement in film direction, Rabindranath Tagore progressively formulated his own ideas of celluloid art and expressed them during the burgeoning of cinema. Although he is regarded highly in adaptation studies, his views on camera, cinema and the cinematic adaptation of literature are not adequately discussed in adaptation/film discourses. Contrary to a general assumption that Indian cinema does not have a film theory of its own, some of his ideas can be connected with the theoretical erudition of cinema studies. However, as most of his pronouncements lie scattered in literary works, it is perhaps important to collate those piecemeal ideas and theorise them in an academic way. Given this background, this paper seeks to study Tagore’s views of cinema and literary adaptation as an instance of early discourse on filmmaking and literary adaptation.